Experimental investigation of Cu@C core-shell nanoparticle suspensions for highly efficient solar-thermal conversion - Chen, Xingyu; Chen, Meijie; Sharaf, Omar Z.; Chen, Wei; Zhou, Ping (Renewable energy, 2024)
The choice of working medium plays a pivotal role in achieving efficient solar-thermal utilization. Nanoparticle suspensions, due to their superior optical and thermal properties, emerge as promising candidates. However, their widespread use is hindered by high costs and a limited absorption bandwidth. In this study, Cu@C core-shell nanoparticles (NPs) were prepared through an experimental process, employing a straightforward in situ polymerization method followed by high-temperature carbonization. Finite element calculations reveals that the solar absorption power of Cu@C NPs surpasses that of C NPs and Cu NPs by 57.2 % and 22.9 %, respectively. This enhancement is attributed to the synergistic coupling between the localized surface plasmon resonance (LSPR) of the Cu core and the robust intrinsic absorption of the C shell. Under 1-sun illumination intensity, experimental findings show that the solar-thermal conversion efficiency (η) of the Cu@C nanoparticle suspension, with a mass fraction of 100 ppm, attains approximately 93 %, tripling that of the water base-fluid (∼31 %). Moreover, both η and the temperature profile exhibit negligible variations under different solar intensities and after repeated heating and cooling cycles, indicating the exceptional stability of the suspensions. These results suggest that Cu@C nanoparticle suspensions present a dependable and efficient solution for solar-thermal applications.